Association between the LACE+ index and unplanned 30-day hospital readmissions in hospitalized patients with stroke - Jun-O'Connell, Adalia H.; Grigoriciuc, Eliza; Silver, Brian; Kobayashi, Kimiyoshi J.; Osgood, Marcey; Moonis, Majaz; Henninger, Nils (Frontiers in Neurology, 2022)
Background: The LACE+ index is used to predict unplanned 30-day hospital readmissions, but its utility to predict 30-day readmission in hospitalized patients with stroke is unknown. Methods: We retrospectively analyzed 1657 consecutive patients presenting with ischemic or hemorrhagic strokes, included in an institutional stroke registry between January 2018 and August 2020. The primary outcome of interest was unplanned 30-day readmission for any reason after index hospitalization for stroke. The 30-day readmission risk was categorized by LACE+ index to high risk (≥78), medium-to-high risk (59-77), medium risk (29-58), and low risk (≤28). Kaplan-Meier analysis, Log rank test, and multivariable Cox regression analysis (with backward elimination) were used to determine whether the LACE+ score was an independent predictor for 30-day unplanned readmission. Results: The overall 30-day unplanned readmission rate was 11.7% (194/1657). The median LACE+ score was higher in the 30-day readmission group compared to subjects that had no unplanned 30-day readmission (74 [IQR 67-79] vs. 70 [IQR 62-75]; p<0.001). On Kaplan-Meier analysis, the high-risk group had the shortest 30-day readmission free survival time as compared to medium and medium-to-high risk groups (p<0.01, each; statistically significant). On fully adjusted multivariable Cox-regression, the highest LACE+ risk category was independently associated with the unplanned 30-day readmission risk (per point: HR 1.67 95%CI 1.23-2.26, p=0.001). Conclusion: Subjects in the high LACE+ index category had a significantly greater unplanned 30-day readmission risk after stroke as compared to lower LACE+ risk groups. This supports the validity of the LACE+ scoring system for predicting unplanned readmission in subjects with stroke. Future studies are warranted to determine whether LACE+ score-based risk stratification can be used to devise early interventions to mitigate the risk for unplanned readmission.